EVALUATION OF LOCAL LANDRACES OF WHEAT FROM DISTRICT BANNU FOR YIELD AND YIELD ATTRIBUTES, KHYBER PAKHTUNKHAWA, PAKISTAN - Mahmood Ur Rehman; Muhammad Bilal; Usra Nazir; Abdul Qadir Khan (International Journal of Contemporary Issues in Social Sciences, 2023)
Wheat is staple food to around the world. In Pakistan people daily consume wheat in the form of bread and various other cookies. In this study 06 different landraces were collected from different areas of District Bannu and evaluated for their yield and yield attributes. The data collected were subjected to Pearson’s correlation and analysis of variance and LSD test. Statistical correlation revealed that the negative impact of plant height on leaves angle. Leaf angle also showed positive effect on panicle length. ANOVA and LSD test revealed that DL heavy and highest yielding landrace in the trial. Therefore, the landrace is recommended for exploitation in District Bannu. The heavier are suggested to be mapped for the candidate genes involved and could be used in any breeding program.